PENINGKATAN KAPASITAS KADER MELALUI PENDEKATAN ACTIVE PATIENT DAN SOCIAL SUPPORT UNTUK ELIMINASI KUSTA DI TALANGO, SUMENEP, MADURA - Abdul Rahem; Anila Impian Sukorini; Yuni Priyandani; Arie Sulistyarini; Andi Hermansyah; Aniek Setiya Budiatin; Toetik Aryani; Sumarno; I Nyoman Wijaya; Gesnita Nugraheni; Ana Yuda; Umi Athiyah; Gusti Noorrizka Veronika Achmad; Mahardian Rahmadi; Farida Ifadotunnikmah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Talango District in Sumenep Regency faces a significant public health challenge, recording the highest leprosy prevalence in the region with 17 active cases in 2024. This issue is deeply rooted in patient non-adherence to long-term medication and the limited clinical capacity of newly appointed village health volunteers. To address this gap, this community service initiative empowered local volunteers through an intensive training program centered on the